Etching of Art Deco buildings - Ghosh, Ayan (Jio Institute, 2023)
Elevation drawings of Palm Court, Oval View and Belvedere Court. The stretch of reclaimed land around Churchgate Station underwent planned development in the 1930s. As a result of strict regulations, Maharshi Karve Marg has a dense concentration of Art Deco buildings, all built in uniform height and use common design idioms.